Afrika Zamani: n°17, 2009 - Full Issue - Journal System, (Afrika Zamani, 2021)
Contents Introduction Penda Mbow & Felistus Kinyanjui ............................................... i Domination and Resistance: Epidemic and Exile in the German Togoland Colony Dennis Laumann ..................................................................................... 1 The Invisible Cohesion of African Leadership: The Lead Up to the 1819 Battle at Grahamstown Reconsidered Julia C. Wells .................................... 17 Strategic Submission as Resistance? Nabongo Mumia in the Struggle for Post-Colonial Kenya's Histories Godwin Siundu ............................................................ 45 Engendering Mauritian History: The Hidden Controversies over Female Suffrage Ramola Ramtohul ................................................................................................ 63 Feminist Activism, Economic Carte Blanche, Political Control, Symbol and Symbolism: A Historical Interpretation of the Kelu Women Revolution in Bu-Cameroon, 1957-59 Henry Kam Kah .................................................. 81 We Are the Sons of Mau Mau! Re-Assessing the Historiography of Resistance in Kenya, 1924-2008 Mwangi J. Macharia ........................................................ 101 Decolonization and Popular Contestation in Sierra Leone: The Peasant War of 1955-1956 Ismail O.D. Rashid .......................................................... 115 The Western Super-Powers and the Liberation Struggle in Africa: The Politics of Imperialism, Domination and Resistance, 1948-1980s Sifiso Mxolisi Ndlovu ......................................................................................... 145 History and Literature/Domination and Resistance: Re-Reading the British-Sudan Afis Ayinde Oladosu ................................................................................ 185 L’artisanat africain entre domination et résistance de la période coloniale à nos jours : le cas de la ville de Maroua au Nord du Cameroun François Wassouni ....... 207 Domination and Resistance through the Prism of Postage Stamps Agbenyega Adedze ......... 227 De la résistance congolaise à la pénétration monétaire européenne (1878-1930) : une véritable guerre des monnaies Guillaume Nkongolo Funkwa .............................. 247 Ecrire l’histoire du mouvement de résistance à la colonisation : un enjeu historiographique à Madagascar Denis Alexandre Lahiniriko ......................................................... 265